Axillary vein thrombosis 30 h after caesarean section: a case report and literature review - Benshuo Cai; Gang Li (BMC, 2022)
Abstract Background Axillary vein thrombosis is a very rare disorder. However, a case of axillary vein thrombosis shortly after caesarean section has not been reported previously. We report a case of axillary vein thrombosis 30 h after caesarean section due to an unidentified aetiology. Case A 37-year-old multiparous woman developed swelling and pain of the forearm and hand 30 h after undergoing a caesarean section. Doppler ultrasonography revealed a 14.9 mm × 5.3 mm thrombosis in the left axillary vein although a prophylaxis of anticoagulation was administrated. After an adjusted-dose of low-molecular-weight heparin (LMWH) was administered, the patient recovered and was discharged. Conclusion Obstetricians should be fully aware of the possibility of upper extremity deep vein thrombosis (DVT) despite its rarity, especially after the surgery. Lying in the lateral decubitus position for long periods postoperatively should be avoided as much as possible.